EFFECTIVENESS OF DEVELOPING TEACHER COMPETENCIES THROUGH SCHOOL PRINCIPALS' TRANSFORMATIONAL LEADERSHIP (RESEARCH AT AL-AMANAH CILEUNYI ISLAMIC PRIMARY SCHOOL) - Munawaroh, Cucu; Ruskandar, Acep; Masruri, G. Ginanjar; Arifin, Bambang Samsul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the effectiveness of developing teacher competency through the principal's transformational leadership. As technology develops and information becomes easily accessible to students, enabling them to learn anything and know anything without the help of a teacher, it is unimaginable that teachers will not develop their competencies. Principal leadership plays a vital role in developing teacher competency. This research was conducted at Al-Amanah Elementary School, Bandung Regency because the Principal applies a transformational leadership style, which is a superior and quality school. The research method used is a descriptive qualitative research method, namely presenting the results of analysis of the types of teacher competency development carried out by the Principal so that they effectively achieve the school's vision and mission. The study results concluded that the transformational leadership characteristics of the Al-Amanah Islamic Elementary School Principal are: 1) As a role model for teachers in carrying out their functions, roles, and responsibilities. 2) Motivating the development of teacher competency through the superior programs provided. 3) Communicative and collaborative in protecting teachers. 4) As a coach who can develop individuals and groups. Principals develop teacher competency through coaching, mentoring, and training activities. Through their transformational leadership style, these three activities effectively develop teachers' competence at the Al-Amanah Cileunyi Islamic Elementary School, making achieving the school's vision easier.